HUBUNGAN STATUS GIZI DENGAN TEKANAN DARAH DAN KADAR HEMOGLOBIN PADA SISWA SMP DI KOTA DENPASAR - Nia Ainiyah; I Putu Suiraoka; G.A. Dewi Kusumayanti (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2019)
Over nutrition or obesity can have an impact on increasing blood pressure through a mechanism of increasing leptin levels, insulin resistance, increased levels of free fatty acids, and activation of the renin-angiotensin-aldosterone system. This study aims to determine the relationship of nutritional status with blood pressure (systolic and diastolic) and hemoglobin levels in middle school students in Denpasar City. This type of research is observational analytic using a cross-sectional design. The sample is 72 people. Data collected by anthropometric measurements, blood pressure measurements and checking hemoglobin levels. Data analysis uses Pearson product moment correlation test. The results showed that there was a significant relationship between nutritional status and systolic blood pressure (p = 0.047), there was no significant relationship to nutritional status with diastolic blood pressure and hemoglobin levels with values (p = 0.091) and (p = 0.185).Keywords: nutritional status, blood pressure, hemoglobin, children